COMPUTATIONAL MODELING OF AERODYNAMIC INTERFERENCE OF HELICOPTER MAIN AND TAIL ROTORS AT THE SPECIAL FLIGHT REGIMES - Y. M. Ignatkin; P. V. Makeev; A. I. Shomov (Научный вестник МГТУ ГА, 2016)
This article is concentrated on modeling and researching of aerodynamic characteristics of main and tail rotors’ combination of a single-rotor helicopter scheme. Non-linear free wake vortical model with diffusion of free wake is used. The model is constructed on the base of Helicopter Design Faculty, MAI. There was analyzed a number of special flight regimes of a helicopter. There were counted aerodynamic characteristics of rotors.